Pelatihan Pengembangan Media Pembelajaran Canva for Education dalam Modul Ajar berbasis Problem Based Learning bagi Guru di SDN Bandungrejosari 2 Kecamatan Sukun Kota Malang - Dewi, Radeni Sukma Indra; Widiyanti, Widiyanti; Chisbiyah, Lismi Animatul; Kusumaningrum, Shirly Rizki; Effendi, Muhammad Idris; Nurlaili, Amaliya Islami; Anjarwati, Rika; Herawati, Megania; Annisa, Ahwatul; Fransisca, Windy (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The Canva for Education training at SDN Bandungrejosari 2 Malang aims to enhance teachers' abilities to create innovative and interactive learning media. This training is essential because many teachers struggle to create engaging and relevant media using modern technology. The training uses the design thinking method, which includes the stages of Define, Ideate, Prototype, and Test. The participants of the training are teachers from SDN Bandungrejosari 2 Malang. Data is collected through surveys, interviews, and observations and then analyzed descriptively. The training results show a significant improvement in teachers' ability to use Canva to create effective learning media. Teachers can identify learning needs, generate creative ideas, and produce engaging and interactive learning media prototypes. Feedback from students indicates that the media created successfully increased their participation and motivation to learn. In conclusion, this training successfully enhanced teachers' technical skills and creativity in using modern design tools and improved the quality of learning at SDN Bandungrejosari 2 Malang.